The Role of the German Red Cross in the Italo-Ottoman War in the Vilayet of Tripolitania (1912–1911) (Comprehensive Journal of Science, 2026)
​This study examines the role of the German Red Cross in the Ottoman-Italian War (1911–1912) in the Province of Tripolitania, as an early model of the intersection of humanitarian work with political and diplomatic dimensions in wartime. The research proceeds from the hypothesis that the German medical mission was not merely a transient relief effort, but constituted an effective instrument of what may be termed 'medical diplomacy', through the advanced medical, organizational, and technical services it rendered in a war environment characterized by blockade and resource scarcity. Employing a historical-analytical methodology and drawing on primary German sources and Turkish Red Crescent archives, the study focuses on the historical circumstances leading to the mission's dispatch, the complex routes taken to reach Gharian via Tunisia, the nature of the field hospital established, and the modern technologies introduced, including X-ray equipment and bacteriological laboratories.
Keywords: German Red Cross, Gharian, Ottoman-Italian War, Province of Tripolitania, Medical Diplomacy